2022
DOI: 10.1039/d2cc04993g
|View full text |Cite
|
Sign up to set email alerts
|

Durable gelfoams stabilized by compressible nanocomposite microgels

Abstract: Although hydrogel microspheres (microgels) are useful as emulsion stabilizers, typical microgels cannot stabilize foams over a prolonged period of time. Here, we found that compressible nanocomposite microgels with solid nanoparticles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In addition, very recently, we found that robust foams can be formed using nanocomposite microgels as stabilizers (Figure , right). A key to creating robust gel foams is to prepare compressible nanocomposite microgels in which the hydrophobic nanoparticles are located near the surface of the parent microgels . To the best of our knowledge, conventional microgels cannot stabilize foams for more than several hours, but in our case, the foams are stable for at least 10 months.…”
Section: Brand-new Type Of Microgels Will Create a New Microgel Sciencementioning
confidence: 87%
See 2 more Smart Citations
“…In addition, very recently, we found that robust foams can be formed using nanocomposite microgels as stabilizers (Figure , right). A key to creating robust gel foams is to prepare compressible nanocomposite microgels in which the hydrophobic nanoparticles are located near the surface of the parent microgels . To the best of our knowledge, conventional microgels cannot stabilize foams for more than several hours, but in our case, the foams are stable for at least 10 months.…”
Section: Brand-new Type Of Microgels Will Create a New Microgel Sciencementioning
confidence: 87%
“…A key to creating robust gel foams is to prepare compressible nanocomposite microgels in which the hydrophobic nanoparticles are located near the surface of the parent microgels . To the best of our knowledge, conventional microgels cannot stabilize foams for more than several hours, but in our case, the foams are stable for at least 10 months. It is worth noting that the method to produce nanocomposites is also useful for fundamental research to clarify various unsolved issues related to microgels .…”
Section: Brand-new Type Of Microgels Will Create a New Microgel Sciencementioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, because of the size of the colloid, they can respond to external stimuli such as temperature and pH changes quickly. 5,9 Considering these features, microgels promise high potential as molecular separation materials, [11][12][13][14] sensors, 15,16 functional catalysts, [17][18][19] interface stabilizers, [20][21][22] and models for colloidal crystals, 23,24 as well as carriers for DDS. 2 In particular, in order to apply microgels as DDS carriers in the body, they must be able to be metabolized after delivering their cargo, 25 and thus, degradable microgels have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…, chemical/biological separation, 2 switchable catalysts, 3 colloidal crystals/glasses, 4 biomedical materials, 5 autonomous actuators, 6 and particulate stabilizers. 7…”
mentioning
confidence: 99%